2017
DOI: 10.1111/jsr.12606
|View full text |Cite
|
Sign up to set email alerts
|

Changes of vitamin D levels and bone turnover markers after CPAP therapy: a randomized sham‐controlled trial

Abstract: The aim was to investigate whether continuous positive airway pressure treatment could modulate serum vitamin D (25-hydroxyvitamin D) and bone turnover markers (collagen-type 1 cross-linked C-telopeptide, osteocalcin and N-terminal propeptide of type 1 collagen) in secondary analysis from a randomized controlled trial. Sixty-five continuous positive airway pressure-naïve male patients with obstructive sleep apnea (age = 49 ± 12 years, apnea-hypopnea index = 39.9 ± 17.7 events h , body mass index = 31.3 ± 5.2 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Liguori et al found increased levels of 25(OH)D after 7 nights of CPAP therapy in male OSA patients, and after 1 year of treatment mainly in obese OSA patients [ 27 , 28 ]. Similar conclusions were reached in a randomized sham-controlled trial, where 24 weeks of CPAP treatment improved Vit D serum levels ( p = 0.045) in patients with severe OSA [ 29 ]. In the present study, Vit D serum levels were strongly associated with AHI.…”
Section: Discussionsupporting
confidence: 75%
“…Liguori et al found increased levels of 25(OH)D after 7 nights of CPAP therapy in male OSA patients, and after 1 year of treatment mainly in obese OSA patients [ 27 , 28 ]. Similar conclusions were reached in a randomized sham-controlled trial, where 24 weeks of CPAP treatment improved Vit D serum levels ( p = 0.045) in patients with severe OSA [ 29 ]. In the present study, Vit D serum levels were strongly associated with AHI.…”
Section: Discussionsupporting
confidence: 75%
“…[79] randomised 64 OSAS patients to either real or sham CPAP treatment for 12 weeks. All participants then received real CPAP therapy for an additional 12 weeks.…”
Section: Cpap Treatment and Vitamin Dmentioning
confidence: 99%
“…We also lacked information on OSA treatment, although prior research suggests that OSA treatment did not change bone turnover markers. ( 69 ) Of note, despite lack of data on OSA severity or nocturnal hypoxia burden, the difference seen by OSA symptoms (eg, EDS and snoring) suggest potential dose–response relationships between OSA severity and VF, providing additional biologic plausibility for this association. Third, our definition of clinical VF required coming to medical attention, which limited our ability to identify asymptomatic cases or confirm certain self‐reported cases (eg, we did not have permission, were unable to obtain the medical record, or there was insufficient evidence in the record to make a definitive VF diagnosis).…”
Section: Discussionmentioning
confidence: 99%